OPTIMALISASI DIKMAS LANTAS DALAM MENGURANGI PELANGGARAN LALU LINTAS OLEH PELAJAR SMA DI POLRES SUMEDANG - agusto Ferdinand (Advances in Police Science Research Journal, 2020)
Traffic violations in Sumedang especially by high school students are a problem that must be faced by the Sumedang Police Traffic Unit especially the Dikyasa unit and to reduce traffic violations along with the high number of violations committed by high school students. The role of Dikmas Lantas is then needed to reduce traffic violations, especially by high school students in Sumedang. This study aims to determine how the description of traffic violations committed by high school students, how the description of Dikmas Lantas activities then reduce traffic violations committed by high school students, and describe the factors that influence the implementation of Dikmas Lantas in Sumedang Regional Police. Research location at Sumedang Regional Police Station. This research uses a qualitative approach with descriptive analysis method. Data collection techniques in this study used data from interviews, observations, and document studies. This study uses the management theory of George R. Terry POAC and 6M theory. The conclusion obtained from this study is there are many types of traffic violations committed by high school students, but what dominates is that related violations do not have a SIM. The description of the activities of the Dikmas Lantas program and its implementation is still not optimal in terms of management theory and Petunjuk Pelaksana Kapolri No.Pol: Juklak / 5 / V / 2003 dated May 29, 2003 concerning the Guidelines for the Implementation of Dikmas Lantas in the Field of Traffic not fully implemented. The inhibiting factors of the implementation of Dikmas Lantas then are in the form of facilities and infrastructure in the implementation of activities are still modest, and the methods provided to the objectives are not yet fully maximized. Suggestions from this research is to conduct planning activities effectively and efficiently, completing facilities and infrastructure to support the implementation of Dikmas Lantas then and give the material more attractive to high school students so it can be easily understood and to understand what will be delivered by the donor material.